Analysis of The Success Level of Pregnancy Women's Classes As A Program To Prevent Maternal and Infant Mortality In Sambirejo Village Langkat Regency - Aisyah Salsabila; Abdul Gafar Parinduri; Humairah Medina Liza Lubis (CV. Inara, 2025)
Maternal and infant mortality remain significant public health challenges worldwide, with preventable causes accounting for approximately 75% of maternal deaths. This study analyzed the success level of the Pregnant Women's Class program as a maternal and infant mortality prevention strategy in Sambirejo Village, Langkat District. This quantitative research employed a cross-sectional analytical survey design with 27 pregnant women at 20-32 weeks gestation. Data were collected using a structured questionnaire containing 20 items assessing maternal knowledge regarding pregnancy, childbirth, and infant care. The Paired Samples t-Test was used to compare pre-test and post-test knowledge scores at a 95% confidence level with alpha 0.05. The results revealed substantial knowledge improvement following program participation, with mean pre-test scores of 73.52 increasing to 92.78 on post-test, representing a 26.2% relative improvement. The Paired Samples t-Test analysis yielded a correlation coefficient of 0.607 with p-value less than 0.001, indicating highly significant knowledge gains. These findings demonstrate that the pregnant women's class program successfully enhanced maternal knowledge about pregnancy, childbirth, newborn care, and postpartum health practices. The pregnant women's class should be integrated as a priority intervention into standard antenatal care packages and expanded across rural Indonesian communities to support maternal and infant mortality prevention efforts.